Relational Trajectories from Parent and Child to Grandparent and New Parent. Issue 2 (3rd April 2017) - Dun, Tim; Sears, Claire
ABSTRACT: This qualitative study follows earlier research of new parents (Dun & Sangster, 2013) to explore grandparents' understanding of communication with their adult children during the arrival of a new generation. In semistructured interviews, 29 grandparents described positive and negative interactions with a child (or child-in-law). Participants graphed changes in the intergenerational relationship with the first-time parents, from the moment the pregnancy was announced through their interview, when the grandchild was up to two years of age. Inductive analysis showed four trajectories, which we describe in detail using informants' reports. Highlighting the volatility of the transition from a parent and child to grandparent and new parent, the most common patterns were Turbulent and Dipped, and the results include variants of these two trajectories. We compare grandparents' retrospectively recalled experiences with the reports of new parents from previous research to facilitate a deeper understanding of intergenerational relationships during a highly unsettled transition.